GEREJA KATOLIK INDONESIA DI TENGAH PUSARAN POLITIK KEKUASAAN DAN TANTANGANNYA KE DEPAN - Donatus Sermada K (Litbang STFT Widya Sasana Malang, 2018)
This article was in fact a lecture delivered by the author on June 10th, 2018 in Surabaya during the national Seminar touching on the Catholic Church in Indonesia and the actual Indonesian political Situation called “Tahun Politik” (Political Year). The author spoke about the Indonesian Catholic Church in the midst of Indonesian political struggle and the future challenges the Catholic Church should face. There were three social-political Phenomenons that have damaged and are still damaging the life of Indonesian nation, including the Indonesian Catholic church, namely the complicated birocratization; the unhealthy politization of the religion and the demoralization of the law. These phenomenons should be taken into account by the Catholic Church, when it comes to concrete commitment of the Catholic Church to give positive impact on Indonesian society based on its own Catholic faith. Artikel ini pada kenyataannya adalah ceramah yang dibawakan penulis pada tanggal 10 Juni 2018 di Surabaya pada kesempatan Seminar Nasional yang bertemakan tentang Gereja Katolik Indonesia dan Situasi aktual politik Indonesia yang disebut “Tahun Politik”. Penulis berbicara tentang Gereja Katolik Indonesia di tengah pergulatan politis dan tantangan-tantangan yang harus dihadapi gereja Katolik ke depan. Ada tiga fenomen sosial-politis yang telah mencederai dan masih sedang mencederai kehidupan berbangsa, termasuk Gereja Katolik, yaitu birokratisasi yang rumit; politisasi yang tidak sehat terhadap agama dan demoralisasi hukum. Fenomen-fenomen itu perlu disikapi gereja Katolik, bila gereja Katolik berkomitmen dalam terang iman Katolik untuk menjawabi tantangan-tantangan itu secara positif demi kebaikan bersama masyarakat Indonesia.